Value Chain Management Model for Retailing of Marine Fish - Kotni, V. V. Devi Prasad (Indian Journal of Marketing, 2018)
The value chain concept addresses various problems being faced by the fisheries sector and its stakeholders. Value chain management enables the policy makers to analyze and assess the marine fisheries sector in a better way and can make the sector more promising and contribute to the development of the economy. The main aim of this study was to analyze various value added operations performed upon the marine fish at the retail point and to examine whether there was any impact of value added operations on the final retail price of marine fish. The primary data of marine fishery retail value chain was collected from the marine fish retailers existing in coastal Andhra Pradesh, India. Finally, it was concluded that there was a difference in price of the marine fish after performing value chain by the retailer. This paper also proposed a retail value chain model for marine fish.